Designing landscapes for grieving children at elementary schools - Thomas, Valerie (Kansas State University, 2013)
Death and loss are natural processes of life, but even so, that does not make them any easier to cope with. For children who may not understand loss, adjusting to life after it can become a nearly impossible feat. Children’s reactions to loss and the grief often include anger, anxiety, confusion, fear, sadness, shock, guilt, and regret (Murthy & Smith, 2005). Nature and art have been used as healing methods in the past, but rarely in schools. Because children spend much of their day at school, outdoor landscapes could be designed to that help alleviate children’s grief and commemorate their memories. This master’s project proposes a set of guidelines and a palette of elements that can be used to create landscapes for grieving in elementary schools. To define these guidelines I combined stages of grieving from two different psychological models with design elements that could help children at each stage of their grief. These guidelines and elements were then tested by applying them at three different elementary schools in Manhattan, Kansas: Marlatt Elementary, Northview Elementary, and Theodore Roosevelt Elementary. The designs at the three elementary schools help illustrate the flexibility of the guidelines and palette of design elements. Not only can the selected elements vary, but the sites can range in size and location. The palette of elements will enable schools to implement landscapes for grieving in a range of places and conditions.
Keywords: Landscape Architecture; Landscapes for Grieving; Landscape Architecture (0390)